2002
DOI: 10.1071/ar01089
|View full text |Cite
|
Sign up to set email alerts
|

Use of tree and shrub belts to control leakage in three dryland cropping environments

Abstract: The water extraction of deep-rooted perennial trees and shrub belts integrated with annual cropping/grazing systems was studied at 3 sites in the 300–450 mm rainfall zone of the Murray–Darling Basin of south-eastern Australia. Within 4 years of planting alley farming systems on cropland, the soil directly below and near the belts had dried the deep profile. Between 82 and 261 mm of extra soil water storage capacity was created in the 2.5 to 5.5–6 m profile. At Palamana (the only site monitored to greater depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…This is consistent with the results of Knight et al (2002) who found a 600 mm deficit under 4 year old Atriplex nummularia-Acacia saligna belts. This drying of the soil profile under perennial mallee stands can be contrasted with the 50-150 mm deficit commonly found for lucerne (Ward and Asseng 2002), the farming system advocated for salinity control in southern Australia.…”
Section: Vertical Extent Of Tree Rootssupporting
confidence: 95%
See 1 more Smart Citation
“…This is consistent with the results of Knight et al (2002) who found a 600 mm deficit under 4 year old Atriplex nummularia-Acacia saligna belts. This drying of the soil profile under perennial mallee stands can be contrasted with the 50-150 mm deficit commonly found for lucerne (Ward and Asseng 2002), the farming system advocated for salinity control in southern Australia.…”
Section: Vertical Extent Of Tree Rootssupporting
confidence: 95%
“…While there are many observations of tree roots at depth (Canadell et al 1996;Stone and Kalisz 1991), the physical and chemical constraints to tree root growth and rate of soil exploration by roots are not well defined. Previous studies have indicated that trees planted on sandy soils can extract water from depths of 8-12 m and prevent recharge laterally from 4 m within 4 years (Dye 1996;Eastham et al 1994;Knight et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This method appears to work best when applied to eucalypts >6 years old in equilibrium with rainfall between 300-700 mm. When the Ellis approach was applied to younger trees, the NRZ predicted from LAI native was greater than that based on measurement of soil water content adjacent to young trees (Knight et al 2002). This may reflect young trees taking up stored water in their immediate vicinity, resulting in fast initial growth and high leaf area, which then reduces as the trees adapt to surviving on rainfall alone and venture out into the adjacent cropped zone in search of water.…”
Section: Influence Of Environmental and Farming System Characteristicmentioning
confidence: 99%
“…In particular, the replacement of trees by annual crops and pastures has decreased annual transpiration rates from vegetation and consequently increased the rate of recharge of aquifers (George et al, 1999;Hatton and Nulsen, 1999;Hatton et al, 2003). Under remnant native vegetation, recharge rates can be as low as 0.1-20 mm y À1 (Allison et al, 1990;Dunin, 1992;Knight et al, 2002) whilst recharge under crops and pasture may be an order of magnitude, or more, larger (Greenwood et al, 1985;Farrington et al, 1992). However, such estimates are based on relatively few measurements, in space and time and do not include comparisons of years receiving above-and below-average rainfall.…”
Section: Introductionmentioning
confidence: 98%